Materiais à base de óxidos com estrutura do tipo perovskite e compósitos como ânodos de PCES - Kolotygin, Vladislav (2015)
This work was focused on the analysis of transport, thermomechanical and electrochemical properties of a series of perovskite-like oxide materials and composites for potential applications as anodes of intermediate-temperature solid oxide fuel cells (SOFCs) with lanthanum gallate and silicate solid electrolytes. The primary attention was centered on A(Mn,Nb)O3-δ (A = Sr, Ca) and (La,Sr)(Mn,Ti)O3-based systems, lanthanum chromite substituted with acceptor-type and variable-valence cations, and various Ni-containing cermets. Emphasis was given to phase stability of the materials, their crystal structure, microstructure of porous electrode layers and dense ceramics, electronic conductivity, Seebeck coefficient, oxygen permeability, thermal and chemical induced expansion, and anodic overpotentials of the electrodes deposited onto (La,Sr)(Ga,Mg)O3- and La10(Si,Al)6O27- based electrolyte membranes. In selected cases, roles of oxygen diffusivity, states of the transition metal cations relevant for the electronic transport, catalytically active additives and doped ceria protective interlayers introduced in the model electrochemical cells were assessed. The correlations between transport properties of the electrode materials and electrochemical behavior of porous electrodes showed that the principal factors governing anode performance include, in particular, electronic conduction of the anode compositions and cation interdiffusion between the electrodes and solid electrolytes. The latter is critically important for the silicatebased electrolyte membranes, leading to substantially worse anode properties compared to the electrochemical cells with lanthanum gallate solid electrolyte. The results made it possible to select several anode compositions exhibiting lower area-specific electrode resistivity compared to known analogues, such as (La,Sr)(Cr,Mn)O3-δ.